Acceptability of thermized shrikhand during storage at refrigeration temperature (8  2  C) - Dhotre, Anant V; Bhadania, Dr AG (Indian Journal of Dairy Science, 2016)
Shrikhand was thermized in a SSHE based continuous shrikhand thermization machine. The sensory attributes of such thermized shrikhand were studied during refrigerated storage at 8 ± 2 °C. Changes occurred in the titratable acidity, consistency and sensory attibutes of the thermized shrikhand during storage were compared with that of unthermized shrikhand taken as control and treated alike except Thermization step. It was found that the thermized shrikhand retained the sensory attributes for longer period than control. Thermized shrikhand also found to retain titratable acidity and consistency (Penetrometer Reading) throughout the storage period. Different combinations TS in chakka Thermization Temperature and Scraper Speed were studied as treatments. The combination of 50 rpm and 70 °C Thermization temperature was found best for the shrikhand prepared from chakka having 19 ± 1 % TS, while the combination of 35 rpm and 70 °C for 1 minute was found best for the shrikhand prepared from chakka having 19 ± 1 % TS. Shrikhand thermized at optimized process parameters was found to give 45 days of shelf life at 8 ± 2°C.